Acute Type A Dissection during Pregnancy with Marfan's Syndrome - Heim, Christian; Müller, Philipp; Weyand, Michael; Harig, Frank (Thoracic and Cardiovascular Surgeon Reports, 2021)
Background Marfan's syndrome (MFS) is a connective tissue disorder, caused by a mutation in the FBN-1 gene and affecting multiple organ systems including the vascular system. During pregnancy, women with MFS have an increased risk of aortic dissection due to changes in the cardiovascular system.
CRIS-Team WoS Importer:2021-04-02

A Dual-Pathogen Mitral Valve Endocarditis Caused by Coxiella burnetii and Streptococcus gordonii—Which Came First? - Kaemmerer, Ann-Sophie; Ciotola, Francesco; Geißdörfer, Walter; Harig, Frank; Mattner, Jochen; Seitz, Tatjana; Suleiman, Mathieu; Weyand, Michael; Heim, Christian (Pathogens, 2023)
Infective endocarditis (IE) is still a life-threatening disease with high morbidity and mortality. While usually caused by a single bacterium, poly-microbial infective endocarditis (IE) is rare. Here, we report a (blood-culture-negative) dual pathogen mitral valve IE caused by Coxiella burnetii and Streptococcus gordonii: A 53-year-old woman was presented to an internal medicine department with abdominal pain for further evaluation. Within the diagnostic work up, transthoracic echocardiography (TTE) revealed an irregularly shaped echogenic mass (5 × 13 mm) adherent to the edge of the posterior mitral valve leaflet and protruding into the left atrium. As infected endocarditis was suspected, blood cultures were initially obtained, but they remained negative. Chronic Q fever infection was diagnosed using serologic testing. After the occurrence of cerebral thromboembolic events, the patient was admitted for mitral valve surgery. Intraoperatively, a massively destructed mitral valve with adhering vegetations was noted. Examination of the mitral valve by broad-range bacterial polymerase chain reaction (PCR) and amplicon sequencing confirmed Coxiella burnetii infection and yielded Streptococcus gordonii as the second pathogen. Based on the detailed diagnosis, appropriate antibiotic therapy of both pathogens was initiated, and the patient could be discharged uneventfully on the 11th postoperative day after a successful minimal-invasive mitral valve replacement.
CRIS-Team Scopus Importer:2023-10-20
Keywords: blood-culture-negative endocarditis; Coxiella burnetii; dual-pathogen endocarditis; endocarditis; minimally invasive mitral valve replacement; polymicrobial infective endocarditis; Q fever; Streptococcus gordonii

A new ex vivo beating heart model to investigate the application of heart valve performance tools with a high-speed camera - Kondruweit, Markus; Friedl, Sven; Heim, Christian; Wittenberg, Thomas; Weyand, Michael; Harig, Frank (Asaio Journal, 2014)
High-speed camera examination of heart valves is an established technique to examine heart valve prosthesis. The aim of this study was to examine the possibility to transmit new tools for high-speed camera examination of heart valve behavior under near-physiological conditions in a porcine ex vivo beating heart model. After explantation of the piglet heart, main coronary arteries were cannulated and the heart was reperfused with the previously collected donor blood. When the heart started beating in sinus rhythm again, the motion of the aortic and mitral valve was recorded using a digital high-speed camera system (recording rate 2,000 frames/sec). The image sequences of the mitral valve were analyzed, and digital kymograms were calculated at different angles for the exact analysis of the different closure phases. The image sequence of the aortic valve was analyzed, and several snakes were performed to analyze the effective orifice area over the time. Both processing tools were successfully applied to examine heart valves in this ex vivo beating heart model. We were able to investigate the exact open and closure time of the mitral valve, as well as the projected effective orifice area of the aortic valve over the time. The high-speed camera investigation in an ex vivo beating heart model of heart valve behavior is feasible and also reasonable because of using processing feature such as kymography for exact analysis. These analytical techniques might help to optimize reconstructive surgery of the mitral valve and the development of heart valve prostheses in future.
EVALuna2:16086

A Practical Approach to Systemic Mastocytosis Complications in Cardiac Surgery: A Case Report and Systematic Review of the Literature - Suleiman, Mathieu; Brückl, Valeska; Fechner, Jörg; Kaemmerer, Ann-Sophie; Wilk, Florian; Weyand, Michael; Harig, Frank (Journal of Clinical Medicine, 2023)
(1) Background: Systemic mastocytosis is a rare, non-curable disease with potential life-threatening complications in patients receiving cardiac surgery. (2) Methods: This systematic review of the literature was prompted by the case of a life-threatening anaphylactic reaction during cardiac surgery related to systemic mastocytosis. The search of all types of studies, using several databases (Pubmed, Scopus and Web of Science), was conducted through September 2022 to identify the relevant studies. (3) Results: Twelve studies were included describing cases of patients undergoing cardiac surgery who were diagnosed with systemic mastocytosis. An adverse effect, namely anaphylaxis, has happened in three cases. Different strategies of premedication, intraoperative and postoperative management were used. In our case, the patient was admitted for elective biological aortic valve replacement due to severe aortic stenosis. Intraoperatively, the patient developed an anaphylactic shock during the administration of protamine after separation from the cardiopulmonary bypass. This anaphylaxis reaction was a complication of the pre-existing systemic mastocytosis and could be successfully managed by the administration of epinephrine, antihistamines and corticosteroids. (4) Conclusions: This systematic literature search and case report highlight the importance of careful preoperative planning, as well as coordination between cardiac surgeons, anesthesiologists and hemato-oncological specialists, in patients with rare but complication-prone diseases such as systemic mastocytosis.
CRIS-Team WoS Importer:2023-03-10

Better Late Than Never - A Case of a Congenital Left Partial Anomalous Pulmonary Venous Drainage Diagnosed and Treated in The Sixth Decade of Life - Elbayomi, Mohamed; Pathare, Presheet; Nooh, Ehab; Harig, Frank; Abdullayev, Farid; Weyand, Michael (Heart Surgery Forum, 2023)
Partial anomalous pulmonary venous drainage (PAPVD) is a relatively uncommon cardiac anomaly. The diagnosis might be challenging as are the presenting symptoms. Its clinical course mimics more familiar diseases, e.g., pulmonary artery embolism. We present a case of PAPVD, which had been misdiagnosed for more than two decades. After establishing the correct diagnosis, the patient got his congenital anomaly surgically corrected and showed excellent cardiac recovery in the six months follow up.
CRIS-Team Scopus Importer:2023-04-07

Bioelectrical Impedance Analysis as a Contemporary Biomarker of Obesity in Adults with Marfan- or Loeys-Dietz-Syndrome - Freilinger, Sebastian; Suleiman, Mathieu; Bischoff, Gert; Ewert, Peter; Freiberger, Annika; Huntgeburth, Michael; Kaemmerer, Ann-Sophie; Schopen, Judith; Meierhofer, Christian; Nagdyman, Nicole; Kaemmerer, Harald; Weyand, Michael; et al. (Reviews in Cardiovascular Medicine, 2022)
Background: It is clinically widely overlooked that many patients with Marfan- (MFS) or Loeys-Dietz-Syndrome (LDS) are obese. While anthropometric routine parameters are not very suitable, the modern Bioelectrical Impedance Analysis (BIA) seems superior for the acquisition of reliable noninvasive assessment of body composition of patients. The aim of the study was to assess the body composition of patients with MFS/LDS by BIA in order to detect occult obesity, which may be a risk marker for aortic or vascular complications. Methods: In this exploratory cross-sectional study, 50 patients (66% female; mean age: 37.7 +/- 11.7 [range: 17-64] years) with a molecular genetic (n= 45; 90%) or clinical (n= 5; 10%) proven diagnosis of MFS or LDS were enrolled between June 2020 and February 2022. All BIA-measurements were performed with the Multifrequence-Impedance-Analyzer Nutriguard-MS (Data Input, Poecking, Germany). Results: The MFS/LDS collective was significantly different from an age-, sex-, and BMI-adjusted control in terms of body fat, percent cell ularity, body cell mass, extra cellular mass/body cell mass index, and phase angle (all p < 0.05). The mean I31A-measured bodyfat was 31.7 +/- 8.7% [range: 9.5.-53.5%], while the mean calculated 13MI of the included patients was 23.0 +/- 4.8 kg/m(2) [range: 15.2-41.9 kg/m(2)]. Therefore, using the obesity cut-off values for the body fat percentage of 25% in men and 35% in women, the BIA classifies as many as 28 patients (56.0%) as obese. In contrast only 12 patients (24.0%) were pre-obese, respectively 3 (6.0%) obese by BMI. The significant difference (p < 0.001) had an accordance of 42.7%. Overall, 15 patients (13 MFS; 2 LDS) had previous aortic surgery (n=14) and/or interventional treatment (n=2) for aortic complications (aneurysm, aortic dissection). 11 out of these 15 (73.3%) were currently classified as obese by BIA. Conclusions: The fact that many patients with MFS or LDS are obese is widely unknown, although obesity may be associated with impaired vascular endothelial function and an increased risk of cardiovascular complications. Also, in patients with MFS/I.DS, INA allows a reliable assessment of the body composition beyond the normal anthropometric parameters, such as BMI. In the future, BIA-data possibly may be of particular i mportance for the assessment of the vascular risk of MFS/LDS patients, besides the aortic diameters.
CRIS-Team WoS Importer:2022-07-22

Calcified Amorphous Tumor and Granulomatosis with Polyangiitis—Case Report and Systematic Review of the Literature - Suleiman, Mathieu; Agaimy, Abbas; Dewald, Oliver; Kaemmerer-Suleiman, Ann-Sophie; Mellert, Fritz; Weyand, Michael; Harig, Frank (Journal of Clinical Medicine, 2025)
Background: Calcified amorphous tumor (CAT) is a rare, mostly incidental tumor-like cardiac lesion of unknown histogenesis. Current imaging modalities do not differentiate between CAT and other masses. As it can be a source for embolization, surgical excision of CAT is mandatory. CAT in patients with Granulomatosis with polyangiitis (GPA) is exceedingly rare. Methods: This systematic literature review was prompted by the case of a CAT in a patient with GPA. The search of all types of studies in two databases (PubMed and Scopus) was conducted through November 2024 to identify the relevant studies. Results: Nine studies were included describing cases of patients being diagnosed with GPA and a cardiac mass. All included patients had a histopathological examination of the either biopsied or surgically resected mass. Only one case reported a CAT. In our case, the patient was diagnosed with GPA through a kidney biopsy, whereas a cardiac mass in the right atrium was diagnosed by echocardiography during evaluation for possible kidney transplantation. One year later a progression was observed, and the mass was resected. The histopathological examination revealed a CAT. The patient could be successfully discharged in a good clinical condition. Conclusions: This systematic literature search and case report highlight the importance of regular echocardiographic examination in patients with GPA. Moreover, surgical excision is crucial for the diagnosis and for further therapy planning, regardless of whether the mass is neoplastic or not.
CRIS-Team Scopus Importer:2025-01-31
Keywords: calcified amorphous tumors; cardiac mass; CAT; granulomatosis with polyangiitis (GPA); Wegener’s granulomatosis

Can we rely on out-of-hospital blood samples? A prospective interventional study on the pre-analytical stability of blood samples under prehospital emergency medicine conditions - Prottengeier, Johannes; Jess, Nicola; Harig, Frank; Gall, Christine; Schmidt, Joachim; Birkholz, Torsten (Scandinavian Journal of Trauma Resuscitation & Emergency Medicine, 2017)
BACKGROUND: Prehospital intravenous access provides the opportunity to sample blood from an emergency patient at the earliest possible moment in the course of acute illness and in a state prior to therapeutic interventions. Our study investigates the pre-analytical stability of biomarkers in prehospital emergency medicine and will answer the question whether an approach of blood sampling out in the field will deliver valid laboratory results. METHODS: We prepared pairs of blood samples from healthy volunteers and volunteering patients post cardio-thoracic surgery. While one sample set was analysed immediately, the other one was subjected to a worse-than-reality treatment of 60 min time-lapse and standardized mechanical forces outside of the hospital through actual ambulance transport. We investigated 21 parameters comprising blood cells, coagulation tests, electrolytes, markers of haemolysis and markers of cardiac ischemia. Bland-Altman analysis was used to investigate differences between test groups. Differences between test groups were set against the official margins of test accuracy as given by the German Requirements for Quality Assurance of Medical Laboratory Examinations. RESULTS: Agreement between immediate analysis and our prehospital treatment is high as demonstrated by Bland-Altman plotting. Mechanical stress and time delay do not produce a systematic bias but only random inaccuracy. The limits of agreement for the tested parameters are generally within clinically acceptable ranges of variation and within the official margins as set by the German Requirements for Quality Assurance of Medical Laboratory Examinations. DISCUSSION: We subjected blood samples to a standardized treatment marking a worse-than-reality scenario of prehospital time delay and transport. Biomarkers including indicators of myocardial ischemia showed high pre-analytical stability. CONCLUSION: We conclude the validity of blood samples from a prehospital environment.
EVALuna2:34204

Comparison of clinical outcome variables in patients with and without etomidate-facilitated anesthesia induction ahead of major cardiac surgery: a retrospective analysis - Heinrich, Stefan; Schmidt, Joachim; Ackermann, Andreas; Moritz, Andreas; Harig, Frank; Castellanos, Ixchel (Critical Care, 2014)
It is well known that etomidate may cause adrenal insufficiency. However, the clinical relevance of adrenal suppression after a single dose of etomidate remains vague. The aim of this study was to investigate the association between the administration of a single dose of etomidate or an alternative induction regime ahead of major cardiac surgery and clinical outcome parameters associated with adrenal suppression and onset of sepsis.The anesthesia and intensive care unit (ICU) records from patients undergoing cardiac surgery over five consecutive years (2008 to 2012) were retrospectively analyzed. The focus of the analysis was on clinical parameters like mortality, ventilation hours, renal failure, and sepsis-linked serum parameters. Multivariate analysis and Cox regression were applied to derive the results.In total, 3,054 patient records were analyzed. A group of 1,775 (58%) patients received a single dose of etomidate; 1,279 (42%) patients did not receive etomidate at any time. There was no difference in distribution of age, American Society of Anesthesiologists physical score, duration of surgery, and Acute Physiology and Chronic Health Evaluation II score. Postoperative data showed no significant differences between the two groups in regard to mortality (6.8% versus 6.4%), mean of mechanical ventilation hours (21.2 versus 19.7), days in the ICU (2.6 versus 2.5), hospital days (18.7 versus 17.4), sepsis-associated parameters, Sequential Organ Failure Assessment score, and incidence of renal failure. Administration of etomidate showed no significant influence (P = 0.6) on hospital mortality in the multivariate Cox analysis.This study found no evidence for differences in key clinical outcome parameters based on anesthesia induction with or without administration of a single dose of etomidate. In consequence, etomidate might remain an acceptable option for single-dose anesthesia induction.
EVALuna2:16090

Continuous Long-Term Assessment of Heart Rate Variability in Adults with Cyanotic Congenital Heart Disease after Surgical Repair - Pieringer, Felix; Suleiman, Mathieu; Kaemmerer-Suleiman, Ann-Sophie; Dewald, Oliver; Freiberger, Annika; Huntgeburth, Michael; Nagdyman, Nicole; Neidenbach, Rhoia; von Scheidt, Fabian; Kaemmerer, Harald; Ewert, Peter; Weyand, Michael; et al. (Journal of Clinical Medicine, 2024)
Background: Heart rate variability (HRV) is an established, non-invasive parameter for the assessment of cardiac autonomic nervous activity and the health status in general cardiology. However, there are few studies on HRV in adults with congenital heart defects (CHDs). The aim of the present study was to evaluate the use of long-term continuous HRV measurement for the assessment of global health status in adults with cyanotic CHD. Methods: This prospective study included 45 adults (40% female, mean age = 35.2 ± 9.2 [range: 19–58] years) after cardiac surgical repair. HRV parameters were calculated from continuous 24 h measurements using a Bittium Faros 180 sensor (Bittium Corp., Oulu, Finland). Results: Postoperative patients with transposition of the great arteries (TGA) (n = 18) achieved significantly higher values of standard deviation of NN intervals (SDNN) (175.4 ± 59.9 ms vs. 133.5 ± 40.6 ms; p = 0.013) compared with patients with other conotruncal anomalies (n = 22). Comparing patients with TGA after a Senning–Brom or Mustard operation (n = 13) with all other heart surgery patients (n = 32), significantly higher HRV parameters were found after atrial switch (root mean square of successive RR interval differences: 53.6 ± 20.7 ms vs. 38.4 ± 18.3 ms; p = 0.019; SDNN: 183.5 ± 58.4 ms vs. 136.3 ± 45.3 ms; p = 0.006). A higher SDNN was also measured after Senning–Brom or Mustard operations than after a Rastelli operations (n = 2) (SDNN: 183.5 ± 58.4 ms vs. 84.5 ± 5.2 ms; p = 0.037). When comparing atrial switch operations (n = 3) with Rastelli operations, the SDNN value was significantly shorter in the Rastelli group (p = 0.004). Conclusions: Our results suggest that continuous HRV monitoring may serve as a marker of cardiac autonomic dysfunction in adults with cyanotic CHD after surgical repair. Impaired cardiac autonomic nervous activity may be associated with an increased risk of adverse reactions in patients with repaired CHD. Therefore, a longitudinal assessment of HRV patterns and trends may provide a deeper insight into dynamic changes in their autonomic regulation and disease progression, lifestyle changes, or treatments. As each person has individual variability in heart rate, HRV may be useful in assessing intra-individual disease progression and may help to improve personalized medicine. Further studies are needed to better understand the underlying mechanisms and to explore the full potential of HRV analysis to optimize medical care for ACHDs.
CRIS-Team Scopus Importer:2024-04-19
Keywords: ACHD; adults with congenital heart disease; arterial switch; atrial switch; cardiac surgery; complete transposition of the great arteries; cyanotic congenital heart defects; heart rate variability; Rastelli operation

Development of a new sternal dehiscence prediction scale for decision making in sternal closure techniques after cardiac surgery - Nooh, Ehab; Griesbach, Colin; Rösch, Johannes; Weyand, Michael; Harig, Frank (Journal of Cardiothoracic Surgery, 2021)
Background: After sternotomy, the spectrum for sternal osteosynthesis comprises standard wiring and more complex techniques, like titanium plating. The aim of this study is to develop a predictive risk score that evaluates the risk of sternum instability individually. The surgeon may then choose an appropriate sternal osteosynthesis technique that is risk- adjusted as well as cost-effective. Methods: Data from 7.173 patients operated via sternotomy for all cardiovascular indications from 2008 until 2017 were retrospectively analyzed. Sternal dehiscence occurred in 2.5% of patients (n = 176). A multivariable analysis model examined pre- and intraoperative factors. A multivariable logistic regression model and a backward elimination based on the Akaike Information Criterion (AIC) a logistic model were selected. Results: The model showed good sensitivity and specificity (area under the receiver-operating characteristic curve, AUC: 0.76) and several predictors of sternal instability could be evaluated. Multivariable logistic regression showed the highest Odds Ratios (OR) for reexploration (OR 6.6, confidence interval, CI [4.5–9.5], p < 0.001), obesity (body mass index, BMI > 35 kg/m2) (OR 4.23, [CI 2.4–7.3], p < 0.001), insulin-dependent diabetes mellitus (IDDM) (OR 2.2, CI [1.5–3.2], p = 0.01), smoking (OR 2.03, [CI 1.3–3.08], p = 0.001). After weighting the probability of sternum dehiscence with each factor, a risk score model was proposed scaling from − 1 to 5 points. This resulted in a risk score ranging up to 18 points, with an estimated risk for sternum complication up to 74%. Conclusions: A weighted scoring system based on individual risk factors was specifically created to predict sternal dehiscence. High-scoring patients should receive additive closure techniques.
CRIS-Team Scopus Importer:2021-06-25
Keywords: Cardiac surgery; Prediction; Scoring system; Sternal dehiscence; Tailored technique

Dysphonia as a Presenting Symptom of a Giant Left Atrial Sarcoma Developing within Five Years - Elbayomi, Mohamed; Nooh, Ehab; Weyand, Michael; Agaimy, Abbas; Harig, Frank (Thoracic and Cardiovascular Surgeon Reports, 2022)
An 83-year-old woman presented with a new onset of dyspnea and dysphonia. Physical examination revealed no abnormalities. Computerized tomography, bidimensional echocardiography, and cardiac magnetic resonance confirmed the presence of a cardiac mass in the left atrium. Surgical resection was uneventful and showed the origin of the mass in the ostium of the left inferior pulmonary vein. Histological evaluation revealed undifferentiated pleomorphic sarcoma with myxoid features. This case highlights the importance of considering cardiac neoplasms as a rare differential diagnosis, including rare and misleading clinical presentations.
CRIS-Team WoS Importer:2022-09-02

Growth of hypoplastic mitral valves in hypoplastic left heart complex and similar constellations after anatomical left superior vena cava correction - Cesnjevar, Robert; Harig, Frank; Dietz, Moritz; Alkassar, Muhannad; Waellisch, Wolfgang; Rueffer, André; Dittrich, Sven; Purbojo, Ariawan (European Journal of Cardio-Thoracic Surgery, 2021)
OBJECTIVES: Left superior vena cava (LSVC)-related obstruction of mitral inflow is a rare finding in patients with complex cardiac anomalies like hypoplastic left heart complex. We report our experience by establishing a left superior to right superior caval vein continuity (innominate vein creation by direct LSVC-right superior vena cava end-to-side-anastomosis), and coronary sinus unroofing if indicated for LSVC-related mitral inflow obstruction. METHODS: Nineteen patients (median age: 1.0 ± 0.3 years; range: 7 days-4.8 years) underwent anatomical correction of LSVC without the use of foreign material in conjunction with repair or palliation of congenital anomalies in a single centre between April 2015 and November 2019. Indications for the procedure were LSVC-related obstruction of left ventricular inflow due to a dilated coronary sinus. Additional procedures included mitral (n = 7) or atrioventricular (n = 3) valve surgery, right ventricular to pulmonary artery conduit (n = 3), first stage palliation (n = 3) or biventricular repair (n = 5) of hypoplastic left heart complex. Three patients needed secondary mitral valve replacement (n = 3). RESULTS: All LSVC or coronary sinus-related obstructions were effectively relieved. No patient died early, 2 patients died late after the procedure. One patient needed stenting of the superior vena cava below the unobstructed cephalad vein anastomosis at the former right superior vena cava-cannulation-site. Follow-up was complete and demonstrated an 89.5% survival after 2.5 ± 0.4 years. Innominate vein patency was 100% documented by echocardiography (n = 19), cardiac catheterization (n = 6) or both. Mean mitral valve z-scores before the operation were -1.7 ± 0.2 (range -3.8 to 0.3) and increased to 0.7 ± 0.2 (range -0.7 to 1.9) after LSVC repair. CONCLUSIONS: Anatomical correction by surgical creation of an innominate vein is an effective method to relieve LSVC-related obstructions and promotes mitral valvar growth. Mitral ring sizes were at least normalized after surgery at the time of discharge. Further prospective follow-up studies to evaluate the growth potential of left-sided heart structures by reporting cardiac z-scores are needed to evaluate the true impact of coronary sinus unroofing.
CRIS-Team Scopus Importer:2021-01-29
Keywords: Congenital heart disease; Hypoplastic left heart complex; Left superior vena cava; Mitral valve growth; Mitral valve z-score

Impact of medical treatment on long-term results after surgical ablation of atrial fibrillation in cardiac surgical patients - Feyrer, Richard; Ballazhi, Fatos; Seitz, Timo; Weyand, Michael; Harig, Frank (Annals of Thoracic and Cardiovascular Surgery, 2014)
The aim of this study was to evaluate the long-term outcome (4 years) of high-intensity-focused-ultrasound (HIFU) cardiac ablation, the significance of postablation antiarrhythmic drugs (AADs) and predictors of successful sinus rhythm (SR) restoration.103 patients were prospectively enrolled in a single-center study. The preoperative atrial fibrillation (AF) type was paroxysmal in 36%, permanent in 53%, persistent in 5% and flutter in 6% patients. The left atrial diameter was <50 mm in 78 patients and >50 mm in 25. Long-term results, up to 4 years, and postablation antiarrhythmics were evaluated. Follow-up studies including 12-lead electrocardiogram (ECG) and 24-h Holter ECG obtained at 3 and 6 months in our institute, and 12, 24, and 48 months during outpatient visits.No device- or procedure-related complications or deaths were observed. A pacemaker was implanted in 5% patients. Freedom from AF and flutter at 6-/12-/and 48-month visit were 66%/63%/68% for the entire population, 84%/77%/90% in patients with paroxysmal AF, 50%/46%/40% in patients with permanent AF and at any time in all 6 patients with flutter. No significant changes were noted at 2 years.Postablation results were not statistically different in patients on or not on antiarrhythmic therapy. At discharge, 53% of patients on antiarrhythmics and 55%, not on AADs were free of AF. At the 6-month visit, 66% of patients on AADs versus 69% of patients, not on AADs presented with SR, an improved outcome by 13 percentage points with AADs versus 14 percentage points without AADs (p = 0.65). Patients taking a ?-blocker showed better results in restoration/maintenance of SR after 6 months. No significant difference was noted regarding the use of UltraWand.Sixty-seven percent with a left atrium (LA) diameter <50 mm were successfully converted into SR, vs. 48% with an LA diameter >50 mm. Best results were achieved in patients with paroxysmal AF and LA <50 mm with 81% freedom of AF.AF treatment with HIFU ablation during concomitant cardiac surgery is a safe and effective procedure for restoring SR, especially in patients with AF and especially in patients with a smaller left atrial diameter. No significant difference was noted between the antiarrhythmic and non drug groups regarding restoration and maintaining SR; however, better results were achieved by those taking a ?-blocker.
EVALuna2:16084

Intraoperative visualization of a deformed left main stent during surgical aortic valve replacement - Müller, Philipp; Heim, Christian; Weyand, Michael; Harig, Frank (Journal of Cardiothoracic Surgery, 2023)
Background: While coronary artery bypass grafting is typically considered first choice for the treatment of left main stenosis, there is a trend towards left main stenting due to a steadily aging population in western countries with a high operative risk and patients with single vessel coronary artery disease affecting the left main artery. Nevertheless left main stenting remains controversial, especially in patients with concomitant indications for open-heart surgery. Case presentation: We want to present a case of a 78-year-old male patient with high-grade aortic stenosis who underwent surgical aortic valve replacement at our heart center due to anatomical contraindications for transcatheter aortic valve replacement. Stenting of the left main coronary artery was performed three years earlier due to single vessel coronary artery disease while moderate aortic valve stenosis was under surveillance at the time of the intervention. Intraoperatively we found the stent to be deformed inside the left main coronary artery, covering nearly 25% of the coronary ostium. So injection of cardioplegia directly into this ostium, as we perform normally, was not possible without further damaging the stent and/or the opening of the ostium. We had to insert cardioplegia via the retrograde way, so via the coronary sinus. Conclusion: While left main stenting can be reasonable for a specific population of patients, it should be used cautiously in patients with concomitant indications for open-heart surgery in the near future and a low perioperative risk profile.
CRIS-Team Scopus Importer:2023-02-10
Keywords: Aortic valve replacement; Cardiac surgery; Cardiology; Coronary artery disease; Left main stenosis; Left main stenting; Stenting

MELD-score for risk stratification in cardiac surgery - Pathare, Presheet; Elbayomi, Mohamed; Weyand, Michael; Griesbach, Colin; Harig, Frank (Heart and Vessels, 2023)
The outcome of the patients undergoing cardiac surgery with cardiopulmonary bypass (CPB) is also influenced by the renal and hepatic organ functions. Risk stratification, using scores such as EURO Score II or STS Short-Term Risk Calculator for patients undergoing cardiac surgery with cardiopulmonary bypass, ignores the quantitative renal and hepatic function; therefore, MELD-Score was applied in these cases. We retrospectively examined patient data using the MELD score as a predictor of mortality. To perform a univariate analysis of the data, patients were classified into three groups based on the MELD Score: MELD < 10 (Group 1), MELD 10 to 19 (Group 2), and MELD ≥ 20 (Group 3). A total of 11,477 participants were included in the study, though several patients with either missing MELD scores or lack of creatinine, bilirubin, or INR levels were dropped from the original cohort. Eventually, 10,882 patients were included in the analysis. The primary outcome was defined as postoperative, in-hospital mortality. Secondary outcomes such as postoperative bleeding, including the requirement for repeat thoracotomy, postoperative neurological complications, and assessment of catecholamines on weaning from cardiopulmonary bypass/ requirement of mechanical circulatory support were examined. A higher MELD score was associated with increased postoperative mortality. Patients with MELD > 20 experienced a 31.2% postoperative mortality, compared to Group 1 (4.6%) and Group 2 (17.5%). The highest rates of postoperative bleeding (13.8%) and, repeat thoracotomy (13.2%) & postoperative pneumonia (17.4%) were seen in Group 3 (threefold increase when compared to Group 1, renal failure requiring dialysis (N = 235, 2.7% in Group 1 v/s N = 78, 22.9% in Group 3) or requiring high dose catecholamines post-operatively or mechanical circulatory support (IABP/ECLS). Incidentally, an increased MELD Score was not associated with a significant increase in the postoperative incidence of stroke/TIA or the presence of sternal wound infections/complications. A higher mortality was observed in patients with reduced liver and renal function, with a significant increase in patients with a MELD score > 20. As the current risk stratification scores do not consider this, we recommend applying the MELD score before considering patients for cardiac surgery.
CRIS-Team Scopus Importer:2023-04-14
Keywords: Cardiac surgery; Liver disease; MELD; Preoperative

Pass On What You Have Learned: A Structured Mentor-Mentee Concept for the Implementation of a Minimally Invasive Mitral Valve Surgery Program - Heim, Christian; Müller, Philipp; Massoudy, Parwis; Harig, Frank; Nooh, Ehab; Weyand, Michael; Czesla, Markus (European Surgical Research, 2021)
Introduction: Starting a minimally invasive cardiac surgery (MICS) for mitral valve repair (MVR) program is challenging as it requires a new learning curve, but compromising surgical results at the same time is not acceptable. Here, we describe our surgical educational experience of starting a new MICS program at a university heart center in Germany. Methods: A dedicated team for the new MICS program including 2 cardiac surgeons, 1 cardiac anesthetist, 1 perfusionist, and 1 scrub nurse was chosen. The use of long shafted instruments was trained in a low-cost self-assembled MICS simulator, and the EACTS endoscopic dry lab course was visited. Thereafter, 1 MICS center was visited for direct observation and peer-to-peer education for 6 weeks. The mentor observed the first 10 cases performed by the mentee. The surgical mitral valve expertise of 1 single cardiac surgeon was retrospectively analyzed between April 2016 and April 2021. Results: Before the implementation of the MICS-MVR program, 18 mitral valve operations have been performed through sternotomy between April 2016 and October 2018 including 12 replacements and 6 ring annuloplasties. After starting the MICS-MVR program, 73 mitral operations have been performed by the same surgeon of which 53 video-assisted through minithoracotomy (72.6%). 83.1% of the MICS procedures included complex repair (n = 38) and ring annuloplasty (n = 6). Open heart MV surgery was necessary in 20 patients due to concomitant procedures (n = 8), redo procedures (n = 2), severe endocarditis (n = 4), or contraindication for MICS such as PAD (n = 6). There have been no deaths, 1 stroke, and 1 cardiac vascular (RCX) complication. Two patients required conversion to sternotomy and one pericardiocentesis in the long term. Conclusion: Typically, excellent exposure and high repair rates of the MV has led us offer MICS approach to a majority of patients with isolated MV disease. Careful planning and a strict mentor-mentee concept facilitated a safe startup of an MICS program in a busy university heart center.
CRIS-Team WoS Importer:2021-12-17

PATHFINDER-CHD: prospective registry on adults with congenital heart disease, abnormal ventricular function, and/or heart failure as a foundation for establishing rehabilitative, prehabilitative, preventive, and health-promoting measures: rationale, aims, design and methods - Freilinger, Sebastian; Kaemmerer, Harald; Pittrow, Robert D.; Achenbach, Stephan; Baldus, Stefan; Dewald, Oliver; Ewert, Peter; Freiberger, Annika; Gorenflo, Matthias; Harig, Frank; Hohmann, Christopher; Holdenrieder, Stefan; et al. (Bmc Cardiovascular Disorders, 2024)
Background: Adults with congenital heart defects (ACHD) globally constitute a notably medically underserved patient population. Despite therapeutic advancements, these individuals often confront substantial physical and psychosocial residua or sequelae, requiring specialized, integrative cardiological care throughout their lifespan. Heart failure (HF) is a critical challenge in this population, markedly impacting morbidity and mortality. Aims: The primary aim of this study is to establish a comprehensive, prospective registry to enhance understanding and management of HF in ACHD. Named PATHFINDER-CHD, this registry aims to establish foundational data for treatment strategies as well as the development of rehabilitative, prehabilitative, preventive, and health-promoting interventions, ultimately aiming to mitigate the elevated morbidity and mortality rates associated with congenital heart defects (CHD). Methods: This multicenter survey will be conducted across various German university facilities with expertise in ACHD. Data collection will encompass real-world treatment scenarios and clinical trajectories in ACHD with manifest HF or at risk for its development, including those undergoing medical or interventional cardiac therapies, cardiac surgery, inclusive of pacemaker or ICD implantation, resynchronization therapy, assist devices, and those on solid organ transplantation. Design: The study adopts an observational, exploratory design, prospectively gathering data from participating centers, with a focus on patient management and outcomes. The study is non-confirmatory, aiming to accumulate a broad spectrum of data to inform future hypotheses and studies. Processes: Regular follow-ups will be conducted, systematically collecting data during routine clinical visits or hospital admissions, encompassing alterations in therapy or CHD-related complications, with visit schedules tailored to individual clinical needs. Assessments: Baseline assessments and regular follow-ups will entail comprehensive assessments of medical history, ongoing treatments, and outcomes, with a focus on HF symptoms, cardiac function, and overall health status. Discussion of the design: The design of the PATHFINDER-CHD Registry is tailored to capture a wide range of data, prioritizing real-world HF management in ACHD. Its prospective nature facilitates longitudinal data acquisition, pivotal for comprehending for disease progression and treatment impacts. Conclusion: The PATHFINDER-CHD Registry is poised to offer valuable insights into HF management in ACHD, bridging current knowledge gaps, enhancing patient care, and shaping future research endeavors in this domain.
CRIS-Team Scopus Importer:2024-04-05
Keywords: ACHD; Adult congenital heart disease; Congenital heart defects; Heart failure; Patient outcomes; Prospective registry

Pericardial tamponade, a diagnostic chameleon: from the historical perspectives to contemporary management - Kaemmerer, Ann-Sophie; Alkhalaileh, Khaleel; Suleiman, Mathieu; Kopp, Markus; Hauer, Christine; May, Matthias; Uder, Michael; Weyand, Michael; Harig, Frank (Journal of Cardiothoracic Surgery, 2023)
Background: Pericardial tamponade (PT) early after cardiac surgery is a challenging clinical entity, not infrequently misrecognized and often only detected late in its course. Because the clinical signs of pericardial tamponade can be very unspecific, a high degree of initial suspicion is required to establish the diagnosis. In addition to clinical examination the deployment of imaging techniques is almost always mandatory in order to avoid delays in diagnosis and to initiate any necessary interventions, such as pericardiocentesis or direct cardiac surgical interventions. After a brief overview of how knowledge of PT has developed throughout history, we report on an atypical life-threatening cardiac tamponade after cardiac surgery. A 74-year-old woman was admitted for elective biological aortic valve replacement and aorto-coronary-bypass grafting (left internal mammary artery to left anterior descending artery, single vein graft to right coronary artery). On the 10th postoperative day, the patient unexpectedly deteriorated. She rapidly developed epigastric pain radiating to the left upper abdomen, and features of low peripheral perfusion and shock. There were no clear signs of pericardial tamponade either clinically or echocardiographically. Therefore, for further differential diagnosis, a contrast-enhanced computed tomography scan was performed under clinical suspicion of acute abdomen. Unexpectedly, active bleeding distally from the right coronary anastomosis was revealed. While the patient was prepared for operative revision, she needed cardiopulmonary resuscitation, which was successful. Intraoperatively, the source of bleeding was located and surgically relieved. The subsequent postoperative course was uneventful. Conclusions: In the first days after cardiac surgery, the occurrence of life-threatening situations, such as cardiac tamponade, must be expected. Especially if the symptoms are atypical, the entire diagnostic armamentarium must be applied to identify the origin of the complaints, which may be cardiac, but also non-cardiac. Central message: A high level of suspicion, immediate diagnostic confirmation, and rapid treatment are required to recognize and successfully treat such an emergency (Fig. 5). Perspective: Pericardial tamponade should always be considered as a complication of cardiac surgery, even when symptoms are atypical. The full range of diagnostic tools must be used to identify the origin of the complaints, which may be cardiac, but also non-cardiac (Fig. 5).
CRIS-Team Scopus Importer:2023-02-17
Keywords: Cardiac tamponade; Diagnostics; Historical aspects; Pericardial effusion; Postoperative complication

Rare Case Report: Left Atrial Sarcoma Obstructing the Left Ventricular Inflow - Kaemmerer, Ann-Sophie; Suleiman, Mathieu; Agaimy, Abbas; Harig, Frank; Weyand, Michael; Tandler, Rene (Journal of Clinical Medicine, 2023)
Malignant cardiac tumors of the heart are extremely rare and may present tremendous diagnostic and therapeutic challenges. These tumors are able to infiltrate the heart and metastasize systemically. Early detection is often elusive as the clinical presentation is highly variable, posing significant diagnostic and therapeutic difficulties. Despite a multidisciplinary approach, the prognosis for patients with malignant cardiac tumors remains guarded. Early diagnosis and a multidisciplinary approach involving cardiac surgeons, oncologists and critical care specialists are crucial in the management of this disease. Further research is needed to better understand the pathomechanisms of tumor-related complications and to develop effective treatment strategies to improve patient outcomes. The rare case of a 78-year-old woman with left atrial tumor requiring emergency surgery for acutely developing mitral valve obstruction is presented. Pathology confirmed an undifferentiated pleomorphic sarcoma. This patient tragically did not survive, highlighting the difficulties of managing such a rare and deceptive heart disease.
CRIS-Team Scopus Importer:2023-11-10
Keywords: cardiac sarcoma; cardiac surgery; left atrial tumor; malignant cardiac tumor; undifferentiated pleomorphic cardiac sarcoma

Single-Center Retrospective Analysis of Acute Type A Aortic Dissection Outcome and Reoperation Focusing on Extended Versus Limited Initial Repair - Elbayomi, Mohamed; Weyand, Michael; Pathare, Presheet; Nooh, Ehab; Harig, Frank (Heart Surgery Forum, 2023)
Background: The optimal management strategy for acute aortic type A dissection remains controversial. Whether a limited primary (index) repair would increase the need for late aortic reintervention is still an open debate.Methods: A total of 393 consecutive adult patients with acute type A aortic dissection who underwent cardiac surgery were analyzed. Our research hypothesis was whether limited aortic index repair (i.e., isolated aorta ascending replace-ment without an open distal anastomosis with and without a concomitant aortic valve replacement, including hemiarch replacement procedure) is associated with a higher incidence of late aortic reoperation compared with extended repair (i.e., any other surgical procedure that goes beyond that limited approach).Results: Type of the initial repair had no statically sig-nificant relationship with in-hospital mortality with a P-value of 0.12, however in multivariable analysis, cross-clamp time had a statistically significant relation with mortality (P = 0.4). From the patients who survived until discharge (N = 311), 40 patients needed a reoperation on the aorta; the mean interval until reoperation was 4.5 years. The relationship between the type of the initial repair and the need for reoperation didn't reach a statically significant value (P = 0.9). In-hospitable mortality after the second operation was 10% (N = 4).Conclusion: We reached two conclusions. 1) An extended prophylactic repair in the initial operation of an acute type A aortic dissection might not lead to a lower incidence of reoperations on the aorta and could increase in-hospital mor-tality by increasing cross-clamp time, and 2) Reoperation on the aorta could be done safely with acceptable mortality outcomes.
CRIS-Team WoS Importer:2023-03-31

Successive surgical repair of a progressive aortic dissection in a case of Loeys–Dietz Syndrome - Pathare, Presheet; Elbayomi, Mohamed; Tandler, Rene; Weyand, Michael; Harig, Frank (Journal of Cardiac Surgery, 2022)
Introduction: The Frozen Elephant Trunk technique is a well-established treatment for aortic dissections (Stanford Type A) involving the aortic arch and descending aorta. The Thoraflex™ Hybrid prosthesis (Vascutek Ltd.), consisting of a proximal flexible conduit and a distal self-expanding covered stent, has consistently shown positive results in the treatment of this condition. Case Description: The following is a description of such a staged reconstruction using the Thoraflex™ Hybrid Ante-Flo™ device, performed in a patient previously diagnosed with Loeys–Dietz Syndrome. After clamping the aorta proximally, an incision was taken at the distal end of the stent. Here, the distal end of the new prosthesis was inserted into the true lumen of the descending aorta and the stent was deployed. Following this, a bypass was established via the left atrium, and blood was returned to the lower body using the perfusion arm of the prosthesis with the proximal part of the descending aorta clamped. The collar of the prosthesis was sutured proximally to the aorta near the inlying previous stent. Air was removed via the perfusion arm of the prosthesis, which was then oversewn. Discussion: To date, hybrid prostheses have only been used on the proximal aorta in patients with aortic aneurysms and aortic dissections (Stanford Type A). Conclusion: Using the described technique, it is possible to reconstruct the aortic anatomy using the available prostheses with accuracy and minimal complications.
CRIS-Team Scopus Importer:2022-12-02
Keywords: aorta and great vessels; perfusion

The lost balloon at midnight: a case report reveals the inevitability of heart team existence - Elbayomi, Mohamed; Weyand, Michael; Nooh, Ehab; Harig, Frank (Journal of Cardiothoracic Surgery, 2023)
BACKGROUND: Dislodgement of a coronary stent-balloon catheter during percutaneous coronary intervention (PCI) is rare but is a life-threatening complication. A 57- year-old male presented with a non-ST elevation myocardial infarction (NSTEMI). Coronary angiography revealed total thrombotic occlusion of the Right coronary artery (RCA). Following the balloon dilatation of the RCA and while trying to retrieve the balloon catheter, the balloon was dislodged from the catheter shaft and entrapped in the coronary vessel. Under cardiopulmonary bypass, with antegrade cardioplegic arrest, the balloon was extracted through a coronary arteriotomy. Right coronary revascularization was done with reversed saphenous vein graft (SVG). DISCUSSION: Given the variety of equipment that can be retained in the coronary artery and the multitude of mechanisms by which it may be entrapped, there are no straightforward techniques applicable to all situations. Specific guidelines or recommendations on properly managing these potentially life-threatening complications do not exist. However, the most crucial issue in the management of these cases is the hemodynamic status of the patient as well as the coronary flow in the vessel with entrapped device or stent. In our case, the RCA was retrogradely perfused from the left coronary artery, which provided time to transfer the patient to cardiovascular surgical backup.
CRIS-Team Scopus Importer:2023-04-21
Keywords: Cardiopulmonary bypass; Case report; Coronary artery bypass surgery; Heart team; Percutaneous coronary intervention; Unstable angina pectoris

The relation of aortic dimensions and obesity in adults with Marfan or Loeys-Dietz syndrome - Suleiman, Mathieu; Freilinger, Sebastian; Meierhofer, Christian; May, Matthias; Bischoff, Gert; Ewert, Peter; Freiberger, Annika; Huntgeburth, Michael; Kaemmerer, Ann-Sophie; Marwan, Mohamed; Nagdyman, Nicole; Roth, Jan-Peter; et al. (Cardiovascular Diagnosis and Therapy, 2022)
Background: Aortic aneurysm and aortic dissection can have a major impact on the life expectancy of Marfan syndrome (MFS) or Loeys-Dietz syndrome (LDS) patients. Although obesity can influence the development of aortic complications, evidence on whether obesity influences the development of aortic aneurysm or dissection in MFS and LDS is limited. The aim of the present study was to elucidate the relationship between aortic size and body composition, assessed by modern bioelectrical impedance analysis (BIA) in MFS/LDS-patients.Methods: In this exploratory cross-sectional study in MFS or LDS patients, enrolled between June 2020 and May 2022, 34 patients received modern BIA and magnetic resonance imaging (MRI) (n=32) or computed tomography (CT) imaging (n=2) of the entire aorta. A P value of <0.05 was considered significant.Results: Fifty-one patients (66% female; mean age: 37.7 +/- 11.7; range, 17-68 years) with MFS or LDS were enrolled; 34 patients, 27 with MFS and 7 with LDS, underwent aortic MRI or CT scanning. The mean aortic length was 503.7 +/- 58.7 mm, and the mean thoracic aortic length and abdominal aortic length were 351.5 +/- 52.4 and 152.2 +/- 27.4 mm, respectively. The aortic bulb and the ascending aorta were measured only in the non-surgically repaired patients. Fifteen MFS (88.2%) and two LDS (40.0%) patients had an aortic aneurysm. In these, the aortic bulb tended to be larger in MFS than in LDS patients [42.6x41.9x41.2 vs. 37.8x37.4x36.8 mm; P=0.07 (-1.1; 9.1); P=0.07 (-1.2; 8.4); P=0.07 (-1.5; 7.9)]. BIA revealed mean body fat levels of 31.6%+/- 8.7% (range, 9.5-53.5%), indicating that 18 patients (52.9%) were obese. There was a significant correlation between body fat content and thoracic aortic length (R=-0.377; P=0.02), muscle mass and total aortic length (R=0.359; P=0.03), thoracic aortic length (R=0.399; P=0.02), extracellular mass (ECM), and total aortic length (R=0.354; P=0.04) , connective tissue and aortic diameters at the aortic arch (R=0.511; P=0.002), aortic isthmus (R=0.565; P<0.001), and abdominal aorta (R=0.486; P=0.004). Older age was correlated with wider aortic arch, isthmus, and abdominal aorta. Male patients had a longer aorta.Conclusions: While a slender habitus is commonly known for MFS and LDS patients, our data show that many MFS and LDS patients (especially female) do not fit this phenotypic characteristic and are obese, which is associated with a more severe aortic phenotype. This topic should be included in the clinical assessment of affected MFS and LDS patients, in addition to measurement of the aortic diameters. Physicians should systematically screen MFS and LDS patients for obesity, educate them about the potential risk of resulting aortic complications, and encourage them to adopt a healthy lifestyle, that includes (mild) exercise and a balanced diet.
CRIS-Team WoS Importer:2023-02-03
Keywords: Adults with connective tissue disease; Marfan syndrome (MFS); Loeys-Dietz syndrome (LDS); body composition; obesity

Treatment of advanced heart failure in adults with congenital heart disease: a narrative review and clinical cases - Sinning, Christoph; Huntgeburth, Michael; Fukushima, Norihide; Tompkins, Rose; Huh, June; Tataneo, Shigeru; Diller, Gerhard-Paul; Chen, Yih-Sharng; Zengin, Elvin; Magnussen, Christina; Kaemmerer, Ann-Sophie; Cho, Yang Hyun; et al. (Cardiovascular Diagnosis and Therapy, 2022)
Background and Objective: The number of adults with congenital heart disease (ACHD) is increasing worldwide. Almost all congenital cardiac lesions can be successfully treated due to the progress in neonatal surgery and pediatric cardiology with a high likelihood of surviving until adulthood. However, ACHD frequently develop sequelae related to the initial cardiac anomaly. Heart failure (HF) is one of the most common complications associated with a high morbidity and mortality.Methods: The authors did search the PubMed database regarding relevant content covering publications up to March 2022. Relevant manuscripts were classified according to the impact factor of the journal, being a guideline manuscript, a position paper by a society or a comprehensive review of the current literature. Key content and findings: Optimal HF treatment remains an unmet need in ACHD. In particular, advanced HF therapy with cardiac resynchronization therapy, ventricular assist devices or organ transplantation is still very different and more specific in ACHD compared to non-ACHD. This review aims to compile international views and evidence from the literatures on the treatment of advanced HF in ACHD. Current challenges, but also the success of different treatment strategies in ACHD are illustrated by clinical cases.Conclusions: The main finding of the review is that data is still scarce regarding ACHD with advanced HF and international efforts to collect data regarding these patients needed to improve the current standard of care.
CRIS-Team WoS Importer:2022-10-21

Wearable cardioverter defibrillator after cardiac surgery: Analysis of real-life data from patients at transient risk of sudden cardiac death - Elbayomi, Mohamed; Weyand, Michael; Seitz, Tatjana; Harig, Frank (Annals of Noninvasive Electrocardiology, 2023)
Background: Especially in the first 3 months after cardiac surgery, patients are at transient risk of sudden cardiac death (SCD). To close the gap between hospital discharge and the final implantable cardioverter-defibrillator (ICD) decision, guidelines recommend temporarily using a wearable cardioverter-defibrillator (WCD) to protect these patients from SCD. We investigated real-life data on the safety, effectiveness, and compliance of the WCD in this population. Methods: Data for analysis were collected via the Zoll Patient Management Network (ZPM) from patients who underwent cardiac surgery and who were discharged with a WCD between 2018 and 2021 at the Cardiac Surgery Center of the University of Erlangen in Germany. Results: The majority of the 55 patients were male (90.9%) and underwent a coronary artery bypass graft (80.0%). The number of patients with left ventricular ejection fraction (LVEF) >35% increased from 9.1% at the beginning of WCD use to 58.2% at the end of WCD use. Six ventricular tachycardia (VT) episodes occurred in four patients. The WCD appropriately defibrillated two patients with VT episodes. There were no inadequate shocks and no fatalities during the observation time. WCD wearing compliance was high, with a median wear time of 23.3 h/day. Conclusion: This retrospective analysis in a single cardiac surgery center confirms prior data on the safety and effectiveness of the WCD in patients in post-surgery care in a real-life setting. The WCD successfully protected patients from SCD during life-threatening VT episodes. WCD wearing compliance was high.
CRIS-Team Scopus Importer:2023-02-17
Keywords: heart failure; sudden cardiac death; ventricular tachycardia; wearable cardioverter defibrillator